ANALISIS PENDAPATAN PETANI KELAPA DI KELURAHAN BENGKOL KOTA MANADO (INCOME ANALYSIS OF COCONUT FARMERS IN THE SUB-DISTRICT OF BENGKOL MANADO CITY) - Indriani ., Limbe; Celsius Talumingan; Caroline Betsi Diana Pakasi (AGRI-SOSIOEKONOMI, 2021)
The purpose of this study was to analyze the income of farmers in Bengkol Village, Manado City. Quantitative data analysis methods to determine the income of coconut farmers in Bengkol Village. The number of respondents 20 0 the sampling was done deliberately (purposive sampling). The results showed that the average income category of farmers who own land and sell coconuts in the form of copra is Rp. 15.654.536 categories of farmers who own land and sell coconuts in the form of coconuts Rp. 773,400 and for the category of farmers who do not own land but have capital to sell coconuts in the form of copra and coconuts Rp. 7,330,500